2020
DOI: 10.1002/ijc.32957
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the adhesion molecule CEACAM1 is associated with early biochemical recurrence in TMPRSS2:ERG fusion‐positive prostate cancers

Abstract: Altered expression of the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) has been linked to adverse tumor features in various cancer types. To better understand the role of CEACAM1 in prostate cancer, we analyzed a tissue microarray containing tumor spots from 17,747 prostate cancer patients by means of immunohistochemistry. Normal prostate glands showed intense membranous CEACAM1 positivity. Immunostaining was interpretable in 13,625 cancers and was considered high in 28%, low in 43% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Alternations of cell adhesion molecules are, on the other hand, involved in the steps of carcinogenesis. [10][11][12][13] Being a kind of tumor suppressor gene, cell-to-cell adhesion is usually reduced or lost during the process of carcinogenesis, 10,11,13,14 which promotes tumor progression and is a prerequisite to carcinoma invasion and metastasis. 13 In our study, with the aim of finding a novel molecular mechanism that forms a spinous structure that is related to extremely strong cell-tocell adhesion in the stratified squamous epithelium, we first produced a broad panel of monoclonal antibodies (MAbs) by immunizing mouse crude squamous tissue samples, then selected through morphological screening a MAb, 11B3, that recognizes the spinous structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternations of cell adhesion molecules are, on the other hand, involved in the steps of carcinogenesis. [10][11][12][13] Being a kind of tumor suppressor gene, cell-to-cell adhesion is usually reduced or lost during the process of carcinogenesis, 10,11,13,14 which promotes tumor progression and is a prerequisite to carcinoma invasion and metastasis. 13 In our study, with the aim of finding a novel molecular mechanism that forms a spinous structure that is related to extremely strong cell-tocell adhesion in the stratified squamous epithelium, we first produced a broad panel of monoclonal antibodies (MAbs) by immunizing mouse crude squamous tissue samples, then selected through morphological screening a MAb, 11B3, that recognizes the spinous structure.…”
Section: Introductionmentioning
confidence: 99%
“…While this spinous structure is thought to derive from the shrinkage of microfilaments between desmosomes, since desmosome‐microfilament structures are rather universally distributed among all kinds of epithelial cells, it is not clear why this particular spinous structure is formed almost exclusively among stratified squamous epithelia. Alternations of cell adhesion molecules are, on the other hand, involved in the steps of carcinogenesis 10‐13 . Being a kind of tumor suppressor gene, cell‐to‐cell adhesion is usually reduced or lost during the process of carcinogenesis, 10,11,13,14 which promotes tumor progression and is a prerequisite to carcinoma invasion and metastasis 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CEACAM1 may play an anticancer role in breast cancer and prostate cancer, and animal experiments have also demonstrated that breast cancer cells or prostate cancer cells overexpressing CEACAM1 have a reduced tumorigenic capacity [ 23 25 ]. In addition, CEACAM1 expression was significantly reduced in breast and prostate cancers and predicts a poor prognosis for these cancers [ 26 , 27 ]. In the present study, we investigated the expression of CEACAM1 in the development and progression of ccRCC and its prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, moderate or strong heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) immunostaining was relevant to positive surgical margin and adverse tumor features ( 21 ). Nevertheless, low or negative expression of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) have linked to PSM in patients with ERG fusion-positive PCa ( 22 ). In addition to the abnormal expression of genes or proteins which included BRCA1-associated protein-1 (BAP1), RNA-binding motif protein 3 (RBP) and Fas-associated death domain-containing protein phosphorylation (FADD) by immunohistochemical analysis, changes of mutational level are also strongly associated with PSM by fluorescence in situ hybridization analysis ( 2 , 23 25 ).…”
Section: Introductionmentioning
confidence: 99%